Asuhan Keperawatan Pada An.V Dengan Dengue Hemoragic Fever (DHF) Grade I Di Ruang Anggrek RSUD Surakarta - Nugroho, Veda Mukti, Siti Arifah, S.Kp., M.Kes (2015)
Background: Dengue hemorrhagic Fever is an infection disease caused by dengue virus, infected by Aides aegypty widespread in the tropics and sub-tropics. Dengue virus infection causes high mortality and morbidity worldwide. Purpose: To implement the nursing in clients with dengue hemorrhagic fever includes assessment, intervention, implementation and evaluation of nursing. Results: Diagnoses that arise in that case; hipertemi associated with the infection; imbalance in nutrition less than body requirements related to inadequate intake, nausea, vomiting; the risk of bleeding associated decrease in the number of platelets (thrombocytopenia). After nursing actions during 3x24jam showed hyperthermia is resolved, the risk of bleeding is not resolved, nutritional imbalance resolved, and the risk of bleeding has not been resolved. Conclusion: The application of nursing care in accordance with the nursing process will achieve good results according with predetermined outcomes. to achieve the success of nursing care required cooperation between health team and the patient or family. Keywords: Dengue hemorrhagic fever, hipertermi, nursing care